A Literary Study Of Chaturvidh Siddhanta And Its Applied Aspect According To Ayurveda Principles - Bishnoi , Mukul Pratap; Baronia, Chandrashri; Mishra, Anshuman (International Research Journal of Ayurveda & Yoga, 2021)
Many experts believe Ayurveda to be the earliest therapeutic discipline. Ayurveda means "Science of Life" in Sanskrit. Ayurvedic wisdom dates back over 5000 years and is frequently referred to as the "Mother of All Healing." There are numerous Siddhant’s in Ayurveda as well, which create a firm basis for the emergence or survival of this living science. Ayurveda’s goal is "Swasthasya swasthya rakshanam aturasy vikar prashamanam," and all Siddhanta is developed and utilised to achieve this goal. According to Acharya Charaka’s Rogbhishagjitiye Adhyaya of Vimaanasthana, Siddhanta is one of the Vaadmarga. All of Ayurveda’s principles are founded on them, which are divided into four types: Sarvatantra, Pratitantra, Adhikarana, and Abhyupagama Siddhanta. A critical analysis of the Chaturvidh Siddhanta of Ayurveda is described in this article with an applied example for a better understanding.